PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS DISCOVERY LEARNING UNTUK MENINGKATKAN MINAT BELAJAR DAN KEMAMPUAN BERPIKIR KREATIF SISWA PADA PELAJARAN MATEMATIKA DI SD - Juli Asmida Rambe; Erika Erika; Riris Nurkholidah Rambe (Jurnal Guru Kita PGSD, 2021)
Abstract: development of discovery learning-based learning tools to increase students' interest in learning and creative thinking skills in mathematics lessons in elementary school. This study aims to develop learning tools based on discovery learning. The purpose of this study was to determine the validity, practicality, and effectiveness of discovery learning-based learning tools to increase students' interest in learning and creative thinking skills in mathematics. The tools developed consist of lesson plans, textbooks and LAS. The population in this study were all fifth grade students of SD Medan Amplas which collected 25 students. This research is a development research. The development process consists of empathy: define, develop, disseminate. From the results of trial I and trial II, it was found that the first learning device developed was valid both in terms of and constructs. The two tools developed were practically used, and the three learning tools developed were effective in terms of the achievement of student learning mastery, student activities within the specified tolerance limits and student responses to learning in the good category. Furthermore, there was an increase in students' interest in learning and creative thinking skills from the first trial and second trial results. From the data that has been obtained shows that discovery-based learning tools in mathematics lessons in elementary school are practical and effective for creative thinking skills and student interest in learning. Keywords: Learning Tools, Discovery Learning, Interest In Learning And Creative Thinking Skills. Abstrak: pengembangan perangkat pembelajaran berbasis discovery learning  untuk meningkatkan minat belajar dan kemampuan berpikir kreatif siswa pada pelajaran  matematika di SD. Penelitian ini bertujuan untuk mengembangkan perangkat pembelajaran berbasis discovery learning. Tujuan penelitian ini untuk mengetahui validitas, kepraktisan dan kefektifan perangkat  pembelajaran berbasis discovery learning untuk meningkatkan minat belajar dan kemapuan  berpikir kreatif matematika siswa. Perangkat yang dikembangkan terdiri dari RPP, buku ajar dan LAS. Popolasi dalam penelitian ini adalah seluruh siswa kelas V SD Medan Amplas yang berjumlah 25 siswa. Penelitian ini merupakan penelitian pengembangan. Proses pengembangan tersebut terdiri dari empat: define, develop, disseminat. Dari hasil uji coba I dan uji coba II diperoleh bahwa pertama perangkat pembelajaran yang dikembangkan valid baik dari segi isi maupun konstruk. Kedua perangkat yang dikembangkan praktis digunakan, dan ketiga perangkat pembelajaran yang dikembangkan efektif dilihat dari ketercapaian ketuntsan belajar siswa, aktivitas siswa dalam batas toleransi yang ditetapkan dan respon siswa terhadap pembelajaran dalam kategori baik. Selanjutnya adanya peningkatan minat belajar dan kemampuan berpikir kreatif  siswa dari uji coba I dan uji coba II Hasil. Dari data yang telah diperoleh menunjukkan bahawa perangkat pembelajaran berbasis discovery learning pada pelajaran matematika di SD adalah praktis dan efektif untuk kemampuan berpikir kreatif dan minat belajar siswa.  Kata kunci : Perangkat Pembelajaran, Discovery Learning,Minat Belajar Dan Kemampuan Berpikir Kreatif.